Promoting economic links between the integration schemes of Latin America and the Caribbean : a CARICOM perspective on selected issues (ECLAC [Port of Spain]TT, 2007)
Discusses trade and trade-related issues and examines Latin American tourist arrivals to CARICOM countries. Focuses on the services industry and analyzes issues related to infrastructure. Deals with production complementation with particular reference to investment. Discusses the Caribbean's involvement in the Andean Development Corporation (CAP).
Bibliography: p. 60-61